PENGARUH BERKARYA SENI TIGA DIMENSI TERHADAP KEMAMPUAN ESTETIS SISWA SEKOLAH DASAR - Nur Fajrie; Bela Setya Pratiwi; Lintang Kironoratri; Imaniar Purbasari (Prima Magistra: Jurnal Ilmiah Kependidikan, 2024)
Based on the results of observations, it shows that teachers have not involved students in direct practice to create three-dimensional works of art. This research aims to determine the effect of creating three-dimensional art on the aesthetic abilities of students in class 2 of SDN 1 Mayongkidul. Researchers use quantitative research. The sampling technique for this research is a saturated sampling technique. The subjects of this research were grade 2 students. The sample obtained in this research was 29 respondents. The data collection technique was carried out using a questionnaire. The data analysis technique in this research is simple linear regression analysis. The results of the research show that there is an influence of creating three-dimensional art on the aesthetic abilities of students in class 2 of SDN 1 Mayongkidul. This is proven by the results of simple linear regression analysis showing that the t value is 13.711 and the t table is 2.052 with a significance value of 0.000 < 0.05. It can be concluded that the t-count value is greater than the t-table (13.711 > 2.052). So, Ho is rejected and H1 is accepted (there is an influence and is significant). So creating three-dimensional art is an independent variable that has a positive and significant influence on the aesthetic abilities of students in class 2 of SDN 1 Mayongkidul. Based on the results of the r2 test or coefficient of determination, there is a positive and significant influence between creating three-dimensional art on the aesthetic abilities of students in class 2 of SDN 1 Mayongkidul of 87.4%, while the remaining 12.6% is influenced by other variables.